1974
DOI: 10.1677/joe.0.0630325
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Plasma Testosterone and Studies on Plasma Corticosteroids in Non-Anaesthetized Male Rhesus Monkeys (Macaca Mulatta)

Abstract: SUMMARY The assays of testosterone and corticosteroids in plasma from adult male rhesus monkeys using competitive protein-binding and radioimmunoassay techniques are described. The radioimmunoassay for testosterone was conducted without chromatography and, therefore, additionally estimated 17β-hydroxy-5α-androstan-3-one (dihydrotestosterone). Levels of testosterone in the peripheral plasma of 14 intact male rhesus monkeys showed marked fluctuations over a period of 24 h. Concentrations of testosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
21
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 0 publications
8
21
0
Order By: Relevance
“…We believe that one of the reasons might be in the methods used to measure the basal cortisol levels. When blood or fecal sampling was used, the sampling time points (29)(30)(31)(32) and the stress caused by the capture and possible environmental disturbances shortly before the collection might have affected the cortisol levels (33)(34)(35).…”
Section: Xiaolimentioning
confidence: 99%
“…We believe that one of the reasons might be in the methods used to measure the basal cortisol levels. When blood or fecal sampling was used, the sampling time points (29)(30)(31)(32) and the stress caused by the capture and possible environmental disturbances shortly before the collection might have affected the cortisol levels (33)(34)(35).…”
Section: Xiaolimentioning
confidence: 99%
“…Primates readily learn to cooperate during injection (Spragg 1940, Levison et al 1964, Priest 1991, Nelms et al 2001, Bentson et al 2003, blood collection (Wall et al 1985, Hein et al 1989, Priest 1990, Reinhardt 2003, saliva collection (Bettinger et al 1998, Tiefenbacher et al 2003, urine collection (Kelly & Bramblett 1981, Anzenberger & Gossweiler 1993, Schnell & Gerber 1997, Lambeth et al 2000, McKinley et al 2003), vaginal swabbing (Bunyak et al 1982, oral drug administration (Turkkan et al 1989, Klaiber-Schuh & Welker 1997, Schnell & Gerber 1997, Crouthamel & Sackett 2004 and topical drug application (Reinhardt & Cowley 1990). Trained subjects show no behavioural signs of fear or distress and the physiological stress response to the procedure is considerably reduced or eliminated altogether (Michael et al 1974, Elvidge et al 1976, Schnell & Gerber 1997, Bentson et al 2003, Reinhardt 2003. 'The least distressing method of handling is to train the animal to co-operate in routine procedures.…”
Section: Alternatives To Restraintmentioning
confidence: 99%
“…Moreover, LH secretion in neonatal castrates, as in males gonadectomized postpubertally, occurs in a distinctly episodic fashion with a frequency of approximately 1 LH pluse/h [15]. Since this mode of gonadotropin secretion is believed to be occasioned by a corresponding intermittent discharge of gonadotropin-releasing hormone (GnRH) by -3, 19] it may be concluded that the hypothala mus of the neonate, like that of the adult, is endowed with the neural oscillator that provides the gondadotrophs with the intermittent hypophysiotropic stimulation that is oblig atory for sustained LH secretion [1], For the foregoing reasons, it was anticipated that the di urnal variation in testicular T secretion, which is characte ristic of sexually mature macaques [5,9,11,14,20] and which results in nocturnal elevations and morning nadirs in the concentration of this plasma steroid, might also be ex tant in the infantile male rhesus monkey. The present study of morning and nighttime T and LH concentrations in the male monkey during the first 8 months of extrauterine life was therefore undertaken.…”
mentioning
confidence: 99%